2022
DOI: 10.1038/s41467-022-33677-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation at birth in monozygotic twins discordant for pediatric acute lymphoblastic leukemia

Abstract: Aberrant DNA methylation constitutes a key feature of pediatric acute lymphoblastic leukemia at diagnosis, however its role as a predisposing or early contributor to leukemia development remains unknown. Here, we evaluate DNA methylation at birth in 41 leukemia-discordant monozygotic twin pairs using the Illumina EPIC array on archived neonatal blood spots to identify epigenetic variation associated with development of pediatric acute lymphoblastic leukemia, independent of genetic influence. Through conditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Childhood ALL exhibits a peak in incidence at the age of 2-5 years, and several experiments have demonstrated that chromosomal abnormalities detected at diagnostic were also identified at birth (such as ETV6-RUNX1, RUNX1-RUNX1T1, and PML-RARA gene fusions, as well as high hyperdiploidy), providing strong support to the prenatal origin of many childhood leukemia subtypes [4][5][6][7][8]. In addition, a recent study on discordant twins for ALL supports a role for DNA methylation alterations in utero impacting leukemogenesis [9]; such DNA methylation patterns may be influenced by periconceptional nutrients including folate [10]. In epidemiologic studies using interview data, prenatal folic acid and vitamin intake from dietary sources and supplementation [11][12][13][14][15] has consistently emerged as a protective factor for childhood leukemia.…”
Section: Introductionmentioning
confidence: 88%
“…Childhood ALL exhibits a peak in incidence at the age of 2-5 years, and several experiments have demonstrated that chromosomal abnormalities detected at diagnostic were also identified at birth (such as ETV6-RUNX1, RUNX1-RUNX1T1, and PML-RARA gene fusions, as well as high hyperdiploidy), providing strong support to the prenatal origin of many childhood leukemia subtypes [4][5][6][7][8]. In addition, a recent study on discordant twins for ALL supports a role for DNA methylation alterations in utero impacting leukemogenesis [9]; such DNA methylation patterns may be influenced by periconceptional nutrients including folate [10]. In epidemiologic studies using interview data, prenatal folic acid and vitamin intake from dietary sources and supplementation [11][12][13][14][15] has consistently emerged as a protective factor for childhood leukemia.…”
Section: Introductionmentioning
confidence: 88%
“…Analysis of the DNA methylome by Illumina EPIC v1 DNAm array derived from the archived neonatal blood spots from MZ twins discordant for paediatric acute lymphoblastic leukaemia (ALL) (n = 41 pairs) revealed 240 DMCs and 10 DMRs consistently associated with ALL risk [ 298 ]. The top four DMCs were validated by methylation-specific droplet digital PCR, with a region overlapping TRIM39 - RPP21 being most significant.…”
Section: Advancing Analysis Of the Dna Methylomementioning
confidence: 99%